SYNTHESIS OF AUTOMATIC CONTROL SYSTEM FOR STEPPING-UP CONVERTER OF DC VOLTAGE AT ACTIVE LOAD OPERATION - A. V. Mironovich; P. P. Primshits (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Investigation of a nontransformer stepping-up converter of dc voltage has been carried out. A non-linear structural circuit of the converter has been developed with the help of the controlled current injection method. A linearization of an object and an automation control system synthesis have been conducted applying method of successive optimization of the circuits. The paper contains results of transient process simulation in the linear computer model and in the power electronics computer model.